Expedient Protocols for the Installation of Pyrimidine Based Privileged Templates on 2-Position of Pyrrolo[2,1-c][1,4]-benzodiazepine Nucleus Linked Through a p-phenoxyl Spacer - Anshu Agarwal; Meenakshi Sharma; Meenakshi Agrawal; D. Kishore (E-Journal of Chemistry)
Exceedingly facile single step expedient protocols based on the versatility and reactivity of corresponding intermediates : [2-(dimethylaminomethylene) ketone] (5) and chalcone (6), derived from 2-(p-acetyl phenoxyl) substituted analogue of pyrrolo[2,1-c][1,4]-benzodiazepine (4), have been developed to provide an easy installation of the pyrimidine based privileged templates at 2-position of pyrrolo[2,1-c][1,4]-benzodiazepine through a p-phenoxyl spacer, by utilizing the synthetic strategy depicted in schemes-1 and 2.